Strengthening the Reading Comprehension of Students using a Context Clue - Oclarit, Rhoderick P; Casinillo, Leomarich F (Journal of Education Research and Evaluation, 2021)
A reading comprehension of a student is the understanding of what is read. The intent of this study is to determine the impact of context clue as intervention for reading comprehension. The study was conducted in 8 elementary schools where the respondents are bona fide Grade 4 learners of San Ricardo District, Southern Leyte, Philippines. The study investigated the effectiveness of context clues as aid for reading comprehension through enhancing student’s vocabulary which utilizes the revised Philippine Informal Reading Inventory (Phil-IRI). Phil-IRI result of the last three years were gathered and found out to be quite low. On the other hand, result of the PHIL-IRI of the current school year (S.Y. 2018-2019) was also gathered and shows to have significant difference to the last three years. Moreover, the pre-test to post-test result shows to have a significant improvement to students’ reading ability. Thus, using context clues have exhibit positive impact to reading comprehension of grade 4 students of San Ricardo District.